A protocol to assess the impact of adding nursing support workers to ward staffing. (29th March 2016) - Duffield, Christine; Roche, Michael; Twigg, Di; Williams, Anne; Clarke, Sean
Abstract: Aim: To assess the impact of adding nursing support workers to ward staffing. Background: Nurses' capacity to provide safe care is compromised by increased workloads and nursing shortages. Use of unregulated workers is an alternative to increasing the number of regulated nurses. The impact of adding nursing support workers on patient, nurse and system outcomes has not been systematically evaluated. Design: A mixed longitudinal and cross‐sectional design using administrative data sets and prospective data from a sample of wards. Methods: Payroll data will identify wards on which unregulated staff work. To assess the impact on nursing‐sensitive outcomes, retrospective analysis of morbidity and mortality data of all patients admitted to Western Australia hospitals for over 24 hours across 4 years will be undertaken. For the cross‐sectional study, a sample of 20 pairs of matched wards will be selected: 10 with unregulated workers added and 10 where they have not. From this sample the impact on patients will be assessed using the Patient Evaluation of Emotional Care during Hospitalisation survey. The impact on nurses will be assessed by a nurse survey used extensively which includes variables such as job satisfaction and intention to leave. The impact on system outcomes will be explored using work sampling of staff activities and the Practice Environment Scale. Interviews will determine nurses' experience of working with nursing support workers. Discussion: The study aims to provide evidence about the impact of adding nursing support workers to ward staffing for patients, staff and the work environment.